Internet-based Cognitive Therapy in the Treatment of Patients with Mental Health Problems in General Practice. A Novel Collaborative Model, 2016 - Kolstrup, Nils (NSD – Norwegian Centre for Research Data, 2018)
In Scandinavian general practice one third of all consultations are due to mental health problems. Many GPs find it difficult to treat psychiatric patients. Specialist mental health care services suffer from many referrals with varying quality. There is a lack of psychiatric specialist health service. Patients will have to wait 3- 6 months for specialist treatment. This delay often aggravates patient symptoms. To overcome varying quality by GPs and referral delay, we need new approaches to patient treatment followed by a more efficient use of the limited resources in the specialized health care. In Northern Norway, 32 % of the population live in rural areas and there is 0,59 psychologist per 1000 inhabitants compared to 1,11 per 1000 in the urban areas of Oslo and Akershus. Long travelling distances to regional hospitals, longer waiting lists, and fewer psychiatric spesialists add to patient sufferings. This also applies to many rural areas in the other Scandinavian countries. By slightly modifying and applying an already existing and well tested internet self help programme for treatment of mental problems and combined with visits to GPs, this project investigated a novel approach of collaboration between patients, GPs and specialist mental health care professionals. The aim was to obtain a more efficient and more qualified patient treatment, better referrals to specialist and safer transition from specialist health care back to GPs. Research question 1: Can the use of the internet-based self-help program BlueMood result in a novel approach of cooperation between patient and general practitioners and yield improved diagnostics and treatment of patients seeking help for depression? Research question 2: Will the use of BlueMood in general practice, result in more efficient referral practices and novel ways of collaboration between GPs and mental health care professionals? Research question 3: Will the use of the BlueMood increase GPs' coping skills in treating patients with mental health problems?